The Effect Of Perceived Social Value On The Competitiveness Of Stanley Tumbler Products In Indonesia:The Mediating Role Of Brand Trust And Brand Reputation - Rahman Maulana; Tommy Christian Efrata (UNIVED Press, 2026)
The development of lifestyle-oriented consumption and social values has driven significant changes in consumer behavior toward premium products. Stanley Tumbler has emerged as a symbol of social consumption that is perceived not only in terms of functional attributes but also through social value, brand trust, and brand reputation. This study aims to examine the effect of perceived social value on the competitiveness of Stanley Tumbler products in Indonesia, with brand trust and brand reputation serving as mediating variables. This study adopts a quantitative approach using a survey method conducted among consumers of Stanley Tumbler products in Indonesia. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that perceived social value has a positive and significant effect on brand trust and brand reputation. Furthermore, brand trust and brand reputation are found to have a positive and significant influence on product competitiveness. Mediation analysis reveals that brand trust and brand reputation significantly mediate the relationship between perceived social value and product competitiveness. These findings emphasize the importance of social value and brand perceptions as key sources of sustainable competitive advantage in the premium lifestyle product market.